Féminismes - Babin, Sylvette; Griffiths, Jennifer; Behiery, Valerie; Buurman, Nanne; St-Gelais, Thérèse; Dubois, Anne-Marie; Toulouse (Esse arts + avis, 2017)
Ce numéro s’intéresse aux rapports singuliers entre l’art et les féminismes. En tenant compte de la multiplicité des subjectivités et de l’hétérogénéité des femmes, il s’agit de faire connaitre comment les multiples pratiques et les théories sur l’art participent à déconstruire les oppressions et les limites liées au genre. On présente une sélection de pratiques féminines et féministes, militantes ou non, issues d’approches et de communautés diverses. Les différentes revendications, prises de position et affirmations témoignent de la diversité des artistes : subversion, soulèvement protestataire, remise en question des archétypes de genre et d’hétéronormativité, approche féministe postcoloniale, résurgence des pratiques ancestrales, représentation de soi, utilisation consciente et assumée de la séduction sont autant de manières de dire, encore, la nécessité des féminismes.
Publisher: Presses de l'Université du Québec à Montréal
Keywords: approches et analyses; art contemporain; artistes féministes; arts; arts visuels et médiatiques; corps; cours; discipline; femmes* artistes; féminisme autochtone; féminisme décolonial; féminisme islamique; har4600; histoire de l'art; intersectionnalité; premier cycle; thématiques

Desire change: contemporary feminist art in Canada - Davis, Heather M. (Heather Margaret); Mentoring Artists for Women's Art (McGill-Queen's University Press ;, 2017)
"In the resistance to the violence of gender-based oppression, vibrant - but often ignored - worlds have emerged, full of nuance, humour, and beauty. Correcting a glaring omission of writing about contemporary feminist work by Canadian artists, Desire Change considers the resurgence of feminist art, thought, and practice in the past decade by examining artworks that respond to themes of diversity and desire. Essays by historians, artists, and curators present an overview of a range of artistic practices including performance, installation, video, textiles, and photography. Contributors address the desire for change through three central frames: how feminist art has significantly contributed to the complex understanding of gender as it intersects with sexuality and race; the necessary critique of patriarchy and institutions as they relate to colonization within the Canadian national-state; and the ways in which contemporary critiques are formed and expressed. The resulting collection addresses art through an activist lens to examine intersectional feminism, decolonization, and feminist institution building in a Canadian context. Heavily illustrated with representative works, Desire Change raises both the stakes and the concerns of contemporary feminist art, with an understanding that feminism is always and necessarily plural."– Provided by publisher.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; arts; canada; cours; discipline; femmes* artistes; féminisme décolonial; har4600; histoire de l'art; histoire et politique; intersectionnalité; patriarcat; premier cycle; périodes historiques; régions géographiques; sexisme; systèmes d'oppressions; thématiques